The Influence of Rewards and Job Embeddedness on Organizational Citizenship Behavior (OCB) in PT Employees. Inalum PLTA Office - Eliza Amalia Saragih; Ainun Mardhiyah (Journal of Finance and Business Digital, 2023)
Employees who behave OCB are certainly assets that can support the company's prospects. OCB behavior must be maintained and fostered by the company with the presence of a reward system. The creation of a pleasant organization and environment also attracts employees to have job embeddedness, which gives them the opportunity to survive and play a role in the company. This research aims to determine the effect of rewards and job embeddedness on OCB in PT employees. Inalum PLTA Office. The analysis technique used is multiple linear regression analysis with statistical tests processed using IBM SPSS 26. The research results show that rewards and job embeddedness have a positive and significant effect on OCB